Pelatihan Mindful Teaching dan Pembelajaran Sosial Emosional untuk Guru Sekolah Dasar - Anita, Yesi; Kenedi, Ary Kiswanto; Febriani, Rahmi Dwi; Yudita, Anisa; Mardin, Asna; Arwin, Arwin; Hamimah, Hamimah; Zuardi, Zuardi (Universitas Pahlawan Tuanku Tambusai, 2025)
This training aimed to enhance elementary school teachers' understanding and skills in applying mindful teaching and developing social-emotional-based learning integrated within deep learning approaches. The program was initiated due to teachers' limited comprehension of embedding emotional and social aspects in thematic instruction. The method included training, lesson plan development workshops, class simulations, implementation mentoring, and pre-post evaluations. Results showed a 59.8% average increase in teacher understanding, along with significant improvement in classroom social interactions and emotional climate. Teachers also successfully developed thematic lesson plans that reflect mindful teaching and SEL principles. This program confirms the importance of integrating mindfulness and social-emotional learning in creating meaningful and emotionally supportive primary education classrooms.